Networking for the Nuts and Bolts: The Ironies of Professional Development for Rural Principals - Aimee Howley; Kristine Chadwick; Caitlin Howley (Journal of Research in Rural Education, 2002)
Early-career rural principals may have more pronounced needs for professional development than thei suburban and urban counterparts, due in part to geographic